PENGARUH PENDIDIKAN PERKOPERASIAN DAN KOMITMEN ORGANISASI TERHADAP PARTISIPASI ANGGOTA KOPERASI CU PUNDHI ARTA - Trisuladana, Rama; Suparman, Aris (Universitas Muhammadiyah Yogyakarta, 2017)
Members in cooperative enterprises have multiple roles, as owners and customers or users, so that the sustainability of cooperative business is dependent on the participation of members. Cooperative education and organizational commitment for most cooperatives have not been considered as an important role to increase member participation. This study aims to determine the influence of cooperative education on the participation of members and the influence of organizational commitment to member participation.Sampling technique in this research use accidental sampling technique with questioner. The analysis used is structural equation modeling (SEM). The population is a member of Cooperative CU Pundhi Arta with a total of 109 respondents. The results showed that cooperative education and organizational commitment had a positive and significant effect on the participation of members in Cooperative CU Pundhi Arta.